2004
DOI: 10.1097/00002030-200401230-00007
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef protein in the nucleus influences adipogenesis as well as viral transcription through the peroxisome proliferator-activated receptors

Abstract: Nef may be involved in both viral replication and the wasting syndrome associated with AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Since Nef suppressed PPARγ expression and reduced fatty acid levels in vitro [29-32], we monitored the expression of PPARγ mRNA and body weights of mice. Significant PPARγ mRNA expression in intestinal adipose tissue of group 3, but not group 1 and 2, was detected on day 2 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Since Nef suppressed PPARγ expression and reduced fatty acid levels in vitro [29-32], we monitored the expression of PPARγ mRNA and body weights of mice. Significant PPARγ mRNA expression in intestinal adipose tissue of group 3, but not group 1 and 2, was detected on day 2 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Nef has also been shown to activate T cells, which increases expression of transcription factors required for viral transcription (31). Recent reports show that Nef directly acts as a positive modulator of HIV-1 LTR through different mechanisms (52,53) and also micro-RNA for nef may down-regulate HIV-1 transcription (54). In our previous study (30), we have shown that Nef enhances viral replication by interacting with its transactivator protein, Tat, and thereby modulates viral gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Ties between resistin and HIV infection have been suggested to be due to the inhibition of PPAR␥ activity by nuclear HIV-1 nef. 39 Indeed, such a contribution by viral accessory proteins to resistin expression would provide a mechanism to explain the observed positive correlation between resistin and viral load. Increases in resistin have been reported in HIV-infected subjects with lipoatrophy, although a relationship between resistin and sTNF RII was not demonstrated.…”
Section: Figmentioning
confidence: 99%